MORPHOLOGICAL ASPECTS OF ENGLISH ADJECTIVAL COMPOUNDS: CORPUS ANALYSIS - Vladimir Ž. Jovanović (Facta Universitatis Series: Linguistics and Literature, 2005)
The paper considers the main formal characteristics of English compound words in adjectival sentence positions, systematized and based on language corpus analysis. The analysis of the compounds along the lines of their composite form, the constituent elements of these words, their interrelationships and other features is accompanied by numerous contextualized examples. The paper provides a statistical confirmation of the fact that compound adjectives make the most prominent group of adjectival compounds (65%), as well as it makes a statement about certain important orthographic implications. Further on, the typical English adjectival compound wouldbe the one with a noun as the first and past participle as the second element of the compound. On the basis of the research conducted here, it can be also concluded that the presence of inflectional morphemes in adjectival compounds is semantically conditioned, and that derivatives only infrequently serve as elements of compoundadjectivals.